1983
DOI: 10.1113/jphysiol.1983.sp014593
|View full text |Cite
|
Sign up to set email alerts
|

Vagal mechanoreceptors located in the lower oesophageal sphincter of the cat.

Abstract: SUMMARY1. In anaesthetized cats, sixty-two vagal sensory units with afferent endings in the lower oesophageal sphincter were recorded by means of extracellular glass micro-electrodes implanted in the nodose ganglion.2. All the receptors had non-medullated fibres, with conduction velocities ranging from 0O8 to 1-2 m/s. From the direct stimulation of the lower oesophageal sphincter, three types of mechanoreceptors were identified. 3. Thirty-one were activated by natural stimuli: tonic contraction of the sphincte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 26 publications
5
46
1
Order By: Relevance
“…Although these results concern the oesophagus, they lead one to suppose that the muscularis mucosae of the LOS plays a role in the closure mechanism of the sphincter. This hypothesis is also supported first by the abundance of vagal mucous mechanoreceptors recently demonstrated in LOS area [Clerc and Mei, 1983a], and sec ondly by the existence of the extension of the muscularis mucosae at LOS level.…”
Section: Muscularis Mucosaesupporting
confidence: 54%
“…Although these results concern the oesophagus, they lead one to suppose that the muscularis mucosae of the LOS plays a role in the closure mechanism of the sphincter. This hypothesis is also supported first by the abundance of vagal mucous mechanoreceptors recently demonstrated in LOS area [Clerc and Mei, 1983a], and sec ondly by the existence of the extension of the muscularis mucosae at LOS level.…”
Section: Muscularis Mucosaesupporting
confidence: 54%
“…The immediate onset of EMRs after TLESRs in the animal model indicates a reflex pathway, and the dependence of the EMR amplitude on the external cuff and endoluminal balloon pressures suggests that mechanoreceptors in the GEJ [20,[32][33][34] play a role in the mediation of post-TLESR EMRs. This hypothesis is supported by the observation that individuals in the control group had as many EMRs as the GERD patients despite significantly fewer TLESRs, as the control group had a significantly higher LESP (which could be interpreted as esophageal outflow obstruction, from the GERD patient's point of view).…”
Section: Discussionmentioning
confidence: 95%
“…This is especially true in the cat, even though it has been used recently as an experimental animal [Biancani et al. 1982;Clerc and Mei. Supported by LSU and UT College of Veterinary Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…1980;Clerc. 1983: Clerc andMei, 1983] and pathology [Bishop el al.. 1979]. Bensley [1902] concluded that the width of the cardiac gland region depends upon the species of animal.…”
Section: Introductionmentioning
confidence: 99%